Efektivitas Salep Ekstrak Daun Sirih Merah (Pipercrocatum) Terhadap Luka Insisi pada Tikus Putih (Rattus norvegicus) - Widyawati, Ratna; Kasy, Ferrini; Yunani, Retina; Pratama, Junianto Wika Adi (VITEK : Bidang Kedokteran Hewan, 2021)
This study aims to see the effectiveness of red betel leaf extract ointment against incision wounds in white rats. The tannin and saponin compounds found in red betel leaf extract function to stimulate the formation of collagen which plays a role in the wound healing process. This study used an experimental research method with the test materials being 21 male white rats (Rattus norvegicus), red betel leaf extract on wound adhesions, the total number of erythrocytes and hemoglobin in white rats due to incision wounds, divided into 3 treatment groups with 7 samples. The results of the mean value of wound attachment in the groups P0 18 ± 0.5, P1 8.5 ± 0.4 and P2 6.5 ± 0.0. The mean results of erythrocyte values in the P0 group were 6.16 ± 0.90a, P1 6.46 ± 0.45a, and P2 6.20 ± 0.63a. and the results of the mean hemoglobin values in the P0 group 11.8 ± 1.1a , P1 12.3 ± 0.7a , and P2 12.1 ± 1.2a . The results of the study showed that the administration of red betel leaf extract ointment (Piper crocatum) on wound attachment had a significant effect at a concentration of 45%, because it was believed that red betel leaf extract ointment could increase peristaltic movements. While the total number of erythrocytes and hemoglobin due to incision wounds in white rats (Rattus norvegicus) there was no significant difference.